2018
DOI: 10.24136/atest.2018.125
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and dynamics of the two stage cycloidal gearbox

Abstract: This article presents results of the numerical analysis of cycloidal gearbox, which were obtained in MSC Adams engineering software. Multibody geometry for dynamical analysis was designed in Autodesk Inventor Professional 2017 and imported in MSC Adams. The results of analysis are forces acting on the internal and external sleeves, position, velocity and acceleration of the selected points on the cycloidal gearbox’s moving components. Indirect result is time course of the torque at output shaft which was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…22
Figure 10.The Y (left) and Z (right) displacement components of points “A” and “B” (Figure 9, right). 22
Figure 11.The Y (left) and Z (right) velocity components of points “A” and “B” (Figure 9, right). 22
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22
Figure 10.The Y (left) and Z (right) displacement components of points “A” and “B” (Figure 9, right). 22
Figure 11.The Y (left) and Z (right) velocity components of points “A” and “B” (Figure 9, right). 22
…”
Section: Resultsmentioning
confidence: 99%
“…22
Figure 11.The Y (left) and Z (right) velocity components of points “A” and “B” (Figure 9, right). 22
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The works [4] and [5] present kinematic analysis of the cycloidal gearbox. There is an incorrect conclusion in [5], where it is stated that the torque fluctuation at the input shaft does not significantly influence output.…”
Section: Current Research In Cycloidal Gearbox Dynamicsmentioning
confidence: 99%
“…The works [4] and [5] present kinematic analysis of the cycloidal gearbox. There is an incorrect conclusion in [5], where it is stated that the torque fluctuation at the input shaft does not significantly influence output. In the current article, it will be shown that torque fluctuation at the output shaft is close to the result of the input torque fluctuation multiplied by the gear ratio (Fig.…”
Section: Current Research In Cycloidal Gearbox Dynamicsmentioning
confidence: 99%